2018
DOI: 10.1039/c8sc00602d
|View full text |Cite
|
Sign up to set email alerts
|

A halogen bond-mediated highly active artificial chloride channel with high anticancer activity

Abstract: Modularly tunable monopeptidic scaffold enables rapid and combinatorial evolution of a halogen bond-mediated highly active chloride channel, exhibiting an excellent anticancer activity toward human breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
89
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 57 publications
2
89
0
3
Order By: Relevance
“…Considerable interest has been invested in developing ion‐transport machinery for selective transport of chloride in lipid bilayer membranes . This endeavor is not only to understand the fundamental transport mechanism in biology but also for possible medical applications in either channelopathies or as anticancer agents . However, synthetic iodide channels are still underexplored, considering that only two iodide‐selective channels have been reported thus far .…”
Section: Introductionmentioning
confidence: 99%
“…Considerable interest has been invested in developing ion‐transport machinery for selective transport of chloride in lipid bilayer membranes . This endeavor is not only to understand the fundamental transport mechanism in biology but also for possible medical applications in either channelopathies or as anticancer agents . However, synthetic iodide channels are still underexplored, considering that only two iodide‐selective channels have been reported thus far .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that halogen atoms form halogen bonds with electron donors and their halogen bonding ability increases from chlorine to bromine to iodine. [20] Although the thyroid hormones,T4and T3, are known to form halogen bonds with their transport proteins transthyretin (TTR) and thyroxine-binding globulin (TBG), [21] it is not known whether halogen bonding is responsible for the cellular uptake of thyroid hormones by MCT8. [18] Although halogen bonds have attracted significant attention in drug discovery, [19] it remains unclear whether they play key roles beyond their applications in improving drug-target interactions.Matile and co-workers and others showed that halogen bonds can be used for ion transport in synthetic membrane systems.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[18] Although halogen bonds have attracted significant attention in drug discovery, [19] it remains unclear whether they play key roles beyond their applications in improving drug-target interactions.Matile and co-workers and others showed that halogen bonds can be used for ion transport in synthetic membrane systems. [20] Although the thyroid hormones,T4and T3, are known to form halogen bonds with their transport proteins transthyretin (TTR) and thyroxine-binding globulin (TBG), [21] it is not known whether halogen bonding is responsible for the cellular uptake of thyroid hormones by MCT8. Thep resent study indicates that halogen bonds may play crucial roles in cellular uptake of organohalogen compounds.T he DFT [22] calculations on the halogenated compounds 4-15 indicate that the halogen bonding ability of the iodo compounds is greater than that of the corresponding bromo or chloro compounds.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Halogen bond (XB) interactions are prevalent in many areas of chemistry, [1][2][3][4][5][6][7] demonstrating important applications in catalysis, [8][9][10][11] crystal engineering [12][13][14] and rational drug design. [15][16][17][18] From a fundamental point of view, it has as well become a topic of main interest in the computational chemistry community. [19][20][21] Politzer and co-workers showed that the halogen lone-pairs, perpendicular to the covalent RÀ X bond, form a belt of negative electrostatic potential, leaving on the extension of the RÀ X bond an area of positive electrostatic potential.…”
Section: Introductionmentioning
confidence: 99%